Special Issues with Single-Payer Health Insurance Systems - Anderson, Gerard F. (World Bank, Washington, DC, 2013)
Health insurance systems have been broadly classified into two groups based on the number of insurance pools: single-payer and multiple-payer systems. In single-payer systems, one organization-typically the government-collects and pools revenues and purchases health services for the entire population, while in multiple-payer systems several organizations carry out these roles for specific segments of the population. This paper examines the organization and operation of single-payer health insurance systems. We classify single-payer systems into four generic models: regional/private, regional/public, central/private, and central/public. The differences between these models are the level of centralization of financing and administration of health care (regional or central) and the ownership of health care providers (mainly public or mainly private). These four models are compared in four topic areas: revenue collection, risk pooling, purchasing, and social solidarity. The single-payer models are then contrasted with systems that use multiple-payer models. The comparisons are made in the same four topics: revenue collection, risk pooling, purchasing, and social solidarity. The paper concludes with a discussion of specific issues for low- and middle-income countries considering a choice between single- and multiple-payer systems.